Minimization, The Trojan Horse of Interviewing? Measuring Perceptions of Witness Interviewing Strategies. (December 2021) - Fallon, Laura; Snook, Brent
Layperson perceptions of explicit and implicit witness interviewing tactics were examined. Canadian residents ( N = 293) read an interview transcript that contained a tactic (i.e., explicit threat or promise, one of four types of minimization, or no tactic) that aimed to persuade the witness to change his account. Participants were then asked to rate the amount of trouble the witness would be in if he (a) changed his account and (b) retained his original account, as well as their perceptions of the witness, interviewer, and tactic. Results showed that participants who viewed a tactic believed the witness would be in less trouble if he changed his account than if he retained his original account. All leniency-related strategies (i.e., explicit leniency and all minimization tactics) were rated as somewhat acceptable and respectful, frequently used, and legal for police to employ. Implications of these findings for witness interviewing are discussed.